KARAKTERISTIKkPOHON TEMPAT TIDUR (night sleeping trees) BEKANTAN (Nasalis larvatus) DI TAMAN WISATA ALAM PULAU BAKUT KABUPATEN BARITO KUALA PROVINSI KALIMANTAN SELATAN - Lisnaini Lisnaini; Abdi Fithria; Gusti Syeransyah Rudy (Jurnal Sylva Scienteae, 2020)
This research was conducted on July 2018 in Pulau Bakut Natural Park, Barito Kuala district, South Kalimantan province.  Primates spend more time in sleeping sites, sleeping sites selection can affect their survival. The variables observed in this study were 6 types, namely tree species, tree height and diameter, tree distance from river bank, number of main branches, tree distance from feed sources and number of sleeping trees. Trees used as sleeping trees by proboscis monkeys did not depend on tree species. Sleeping trees were on the edge of the island between 0-15 m from the river. The selected sleeping trees of proboscis monkeys had relatively large stems (between 23.57 to 92.36 cm) and were relatively high (10—35 m) with many branches, overlapped each other, thus created connectivity with the surrounding vegetation. The sleeping trees of proboscis monkeys identified during the study period were 2 (two) species, namely Sonneratia caseolaris (sea rambai/red pidada) and Fagraea crenulata (moon wood). The selection of sleeping trees on the river bank was a proboscis monkey's strategy to avoid predators, avoid parasites from their feces, reduce injuries due to falls, facilitate social interaction and motion efficiencyKeywords: Proboscis monkeys; Nasalis larvatus; night sleeping trees; bakut island